Comparison of databases reporting nutrient measures of fish and other aquatic foods - Cohen, Philippa; Consalez, Fabio; Ahern, Molly; Masangwi, Sitilitha; Rittenschober, Doris; Holmes, Bridget; Kjellevold, Marian; Golden, Christopher; Hicks, Christina (WorldFish, 2023)
The nutrition values of fish and other aquatic foods have recently gained global recognition for their potential to alleviate ‘hidden hunger’ in many contexts and for many nutritional vulnerable people. Yet, data for most fish, aquatic species, and forms of aquatic foods (particularly those of lower commercial value) are unavailable and unattainable due to the prohibitive cost of high-quality nutrient analysis. This means the databases that house the data that do exist are simultaneously incredibly valuable and riddled with gaps. Many initiatives have risen to address this challenge of compiling the best quality, to all available, data on the nutrient qualities of fish and other aquatic foods. There are multiple databases that now exist through which a researcher or policy maker might locate or contribute data. These include (1) Analytical Food Composition Database; (2) Food Composition Database for Biodiversity Global food composition database for fish and shellfish (3) Seafood Data (4) FishNutrients (5) Aquatic Food Composition Database (6) FoodEXplorer (7) the many different National Food Composition Databases. With input from experts from the fields of food sciences, nutrition and fisheries, and with a rapid review process by database curators, we compiled the metadata for seven different databases that contain large data set on nutrient qualities of fish and other aquatic foods. By summarising metadata, and generating a comparison between databases, we envisage that this tool will help researchers navigate these different tools, and better understand their different strengths and limitations.